Prehospital blood pressure lowering in patients with ultra-acute presumed stroke: A systematic review and meta-analysis. - Yuyang Liu; Yaheng Tan; Jun Wan; Yangchun Xiao; Qiwen Chen; Yuxin Zheng; Chengli Tian; Xinyue Wang; Wenhao Xu; Xueying Yu; Dianxiang Lu (PLoS ONE)
Objective High blood pressure frequently occurs in the setting of acute stroke and is associated with worse prognoses. However, it is still uncertain whether initiating blood pressure-lowering therapy in the prehospital phase after stroke onset can enhance outcomes for patients with undifferentiated acute stroke. Methods We conducted a search of the PubMed, Embase, and Cochrane databases to identify randomized controlled trials investigating prehospital blood pressure lowering interventions for presumed ultra-acute stroke (within <6 hours). The primary outcome analyzed was the 90-day modified Rankin Scale (mRS), while mortality was considered a secondary outcome. Results This meta-analysis included four studies with a total of 3912 patients. The pooled data revealed no significant difference in poor functional outcomes at 90 days (RR = 0.97, 95% CI: 0.92-1.02) or mortality rates (RR = 1.02, 95% CI: 0.90-1.15) between the group receiving blood pressure lowering treatment and the control or placebo group. Conclusions In patients with ultra-acute presumed stroke, prehospital blood pressure lowering treatment within 6 hours of stroke did not improve clinical outcomes (PROSPERO: CRD42024557505).